KINERJA BADAN KEPEGAWAIAN, PENDIDIKAN, DAN PELATIHAN KABUPATEN LANDAK - Grigchella Yolanda Putri E.42009051 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2013)
This essay is making for to produce a understanding about employee job result especially in government service management. The problem is about service management through BKPP is an interesting problem to research because still many people especially civil servant in Landak regency complain about instance responsiveness, responsibility and service quality that given by BKPP. Through this essay, in order to the process service management can optimal for the sake of realization of first rate service for people especially civil servant can enjoy the public service so there isn’t a negative thinking that given. Bureaucracy performance include three things, they are : responsibility, is a responsiveness from the government instance toward service management that given by people through responsiveness, hospitality and facility. Accountability, is a service that can be guarantee appropriate with legislation rules. Service quality, is an admirable mental claim and attitude when the service implementation can solve better, clearly and timely. Keywords : bureaucracy performance, service management, responsibility, accountability, service quality.